A Survey on Data Dissemination and Routing Protocol in VANET: Types, Challenges, opportunistic and Future Role - Mustafa Maad Hamdi, Lukman Audah, Sami Abduljabbar Rashid, Ahmed Shamil Mustafa, Mohammed Salah Abood (International Journal of Advanced Science and Technology, 2020)
Vehicles ad hoc networks (VANETs) have arisen as an interesting area of study and implementation. To ensure smart connectivity for vehicle networks, VANETs may enhance the reliability and productivity of road traffic exceptionally. A distribution of data in the VANET system is an extremely difficult challenge because of fast adjustments and recurrent fragmentation of the network.in this paper, we survey on explain this review on three parts. In the first part, we will show the concept of data dissemination and explain all their types. in the second part, we will provide a comprehensive review on kinds of routing protocols, finally, the third part, we will discuss some of the issues and challenges. Keywords: VANET, Data Dissemination, routing protocols, V2V, V2I, V2R.